1997
DOI: 10.1038/nbt0597-448
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fluxes in riboflavin-producing Bacillus subtilis

Abstract: The pentose phosphate pathway and the pyruvate shunt were identified as major pathways of glucose catabolism in a recombinant, riboflavin-producing Bacillus subtilis strain. Reactions connecting the tricarboxylic acid cycle and glycolysis, catalyzed by the malic enzyme and phosphoenolpyruvate carboxykinase, consume up to 23% of the metabolized glucose. These are examples of important fluxes that can be accessed explicitly using a novel analysis based on synergistic application of flux balancing and recently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
317
3
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 270 publications
(338 citation statements)
references
References 27 publications
17
317
3
1
Order By: Relevance
“…The system of linear equations was solved uniquely with constraints obtained from six of the above calculated flux ratios (i.e. serine through glycolysis, pyruvate through Entner-Doudoroff pathway (ED pathway), oxaloacetate from phosphoenolpyruvate (PEP), PEP from oxaloacetate, pyruvate from malate, and PEP through PP pathway) that were formulated as linearly independent equations as described previously (23,39,40). Briefly, the sum of the weighed square residuals of the constraints from both metabolite balances and flux ratios was minimized by using the MATLAB function fmincon, and the residuals were weighed by dividing through the experimental error (39).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system of linear equations was solved uniquely with constraints obtained from six of the above calculated flux ratios (i.e. serine through glycolysis, pyruvate through Entner-Doudoroff pathway (ED pathway), oxaloacetate from phosphoenolpyruvate (PEP), PEP from oxaloacetate, pyruvate from malate, and PEP through PP pathway) that were formulated as linearly independent equations as described previously (23,39,40). Briefly, the sum of the weighed square residuals of the constraints from both metabolite balances and flux ratios was minimized by using the MATLAB function fmincon, and the residuals were weighed by dividing through the experimental error (39).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, organisms lacking transhydrogenases, such as the yeast Saccharomyces cerevisiae, cannot tolerate imbalances between catabolic NADPH production and anabolic NADPH consumption (18,19), unless a soluble isoform is expressed (19,20). Further means of NADPH reoxidation must exist, however, because isotopic tracer-based carbon flux analysis revealed that at least some bacteria without transhydrogenase homologues exhibit a similar uncoupling (21)(22)(23)(24)(25). In Escherichia coli, overexpression of the soluble transhydrogenase UdhA was shown to partially restore the growth phenotype of a phosphoglucose isomerase mutant with impaired NADPH metabolism (26), but its phys-iological role in wild-type E. coli remains obscure.…”
mentioning
confidence: 99%
“…This requires assumptions on the energy metabolism [Y ATP , stoichiometry of oxidative phosphorylation (P/O) ratio, NADH balance, NADPH balance]. Stoichiometric parameters such as P/O ratios or ATP-yields, often originate from wild type strains and continuous cultures and may not hold true in cases of highly engineered strains [5]. Moreover, such parameters may not stay constant during batch cultivations with changes of the physiological status of the cells.…”
mentioning
confidence: 99%
“…Such analytically deduced flux ratios were also used successfully as constraints for metabolic flux analysis [13][14][15]. Based on probabilistic equations, a more general methodology was developed to simultaneously identify network topology and multiple flux partitioning ratios [16,17].…”
mentioning
confidence: 99%